Pengaruh Islamic Marketing dan Islamic Branding Terhadap Purchase Intention Teh Celup Merek Lipton di Indonesia - Afiyat Isna Haqiqi (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of Islamic Marketing and Islamic Branding on the Purchase Intention of Lipton brand tea bags in Indonesia. The population of this study is Indonesian people who are Muslim and know and are interested in Lipton brand tea bags. The data collection method in this study uses a survey method. The data collection technique uses a questionnaire or online survey technique via google form with a data collection tool in the form of a questionnaire. In this study using a sample of 100 people with a sampling method using porpusive sampling. The type of research used in this study is causal associative. Processing of data in this study using SPSS by conducting various tests such as validity test, reliability test, classical assumption test, multiple linear analysis test, t test, f test, and coefficient of determination test. The results of this study indicate that Islamic Marketing (X1) has a positive and insignificant effect of 15.3% on Purchase Intention (Y) and Islamic Branding (X2) has a positive and significant effect of 89.9% on Purchase Intention (Y). Based on the results of this study, it is recommended that Lipton companies continue to improve company strategies using Islamic Marketing and Islamic Branding so as to increase Purchase Intention in Muslim consumers in Indonesia.